2020
DOI: 10.1002/2475-8876.12151
|View full text |Cite
|
Sign up to set email alerts
|

Optimal structural restoration of historic building in Japan considering lifecycle seismic loss analysis

Abstract: An economic performance evaluation scheme of historic buildings that consider the effect of structural renovation is proposed to provide information facilitating to the selection of reasonable renovation methods for preserving historic buildings. Ground motion scenarios, herein referred to as "lifecycle earthquake scenarios" in accordance with the previous research, were simulated to represent the annual maximum earthquake intensity data from the year of decision-making until the end year of the building's lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was revealed that highly accurate damage detection results could be obtained by shooting at a subject distance of 50 cm using a smartphone with approximately 12 million effective pixels (pixel pitch of about 1.5 μm). In the future, we plan to conduct additional shooting experiments under various outdoor environmental conditions to examine the validity and versatility of the appropriate shooting parameters obtained in this paper. It can also be applied to the optimal repair design technique 48 based on seismic reparability performance, since the surface damage of nonstructural finish itself is directly related to the cost of repair. On the contrary, to evaluate the residual seismic performance, it is important to establish a theoretical mechanism for the correlation between the surface damage and the experienced inter‐story drift ratio focusing on the drift ratio of the exterior finish itself and previous findings, because the construction condition, external force action, and boundary conditions greatly affect the damage level of the exterior finish.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that highly accurate damage detection results could be obtained by shooting at a subject distance of 50 cm using a smartphone with approximately 12 million effective pixels (pixel pitch of about 1.5 μm). In the future, we plan to conduct additional shooting experiments under various outdoor environmental conditions to examine the validity and versatility of the appropriate shooting parameters obtained in this paper. It can also be applied to the optimal repair design technique 48 based on seismic reparability performance, since the surface damage of nonstructural finish itself is directly related to the cost of repair. On the contrary, to evaluate the residual seismic performance, it is important to establish a theoretical mechanism for the correlation between the surface damage and the experienced inter‐story drift ratio focusing on the drift ratio of the exterior finish itself and previous findings, because the construction condition, external force action, and boundary conditions greatly affect the damage level of the exterior finish.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of new materials and the development of innovative devices enable higher levels of comfort and efficiency, which eventually evolve into legal requirements. In recent years, the focus on architectural rehabilitation has been particularly focused on aspects such as energy efficiency [1][2][3][4][5] and structural stability [6][7][8][9]. In relation to the first topic, studies such as the one conducted by D'Adamo et al [5] demonstrate the cost-effectiveness of integrating renewable energy sources into existing public buildings.…”
Section: Introductionmentioning
confidence: 99%